Digital Transformation and Renewable Energy Adoption in the MENA Region: An Econometric Analysis - Yemmen, Jihene (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of digital transformation on the adoption of renewable energy sources. It employs the Cross-Sectionally Augmented Autoregressive Distributed Lag model and conducts robustness checks using the Fully Modified Ordinary Least Squares approach to assess the potential influence of errors or random variations in the data. The analysis covers 12 countries in the MENA region from 2010 to 2023. The results indicate that digital transformation has a positive and statistically significant effect on the share of renewable energy. Governance quality emerges as a key determinant, whereas urbanization exhibits a negative correlation. This research contributes to the literature by providing novel empirical evidence for a region characterized by hydrocarbon dependency. It highlights the need for integrated policies that combine digital development, institutional strengthening, and the management of urban expansion to accelerate the energy transition.